Evaluasi Perencanaan Persediaan Antibiotik Secara Kuantitatif Di Instalasi Farmasi Rumah Sakit Tipe A - Venna Laurensia; Gusti Noorrizka Veronika Achmad; Raswita Diniya; Ivonne Soeliono (Faculty of Pharmacy, Universitas Gadjah Mada)
Planning an inventory of antibiotics that are not good will cause problems in planning, which are over-supply of antibiotics (stagnant) and lack of antibiotic stock (stockout). In this study an quantitative evaluation of antibiotic inventory planning was carried out using the Economic Order Quantity (EOQ) and Maximum-Minimum Stock Level (MMSL) control methods in 2017 at Type A Hospital’s Pharmacy Department. The EOQ method aims to minimize the number of orders while the MMSL method is used to determine the minimum and maximum stock of antibiotics that must be ordered. The results were compared with the need for 2018 then calculations are carried out to determine the amount of stagnant and stockout antibiotics. The number of antibiotics that were stagnant by EOQ method simulation was 44.73% and by MMSL method was 48.02%, while the number of antibiotics stocked by EOQ method was 38.15% and by MMSL method was 42.76%. The category of antibiotic supplies in 2018 in real terms which was included in a stagnant state was 23.68%, stockout ie 55.26% of 152 antibiotics. Evaluation of antibiotic inventory planning using the EOQ method results in the calculation of lower order quantities while the number of orders with MMSL is higher. To find out more broadly about the evaluation of inventory planning in the hospital needed further research by taking into account all drugs not just antibiotics.